Nursing Students’ Perceptions of English Online Learning - Darius Yonatan Nama; Viktorius P. Feka; Novitha Shandra J. Neno (MO.RI Publishing, 2023)
This study aimed to explore the perceptions of fourth-semester students of the nurse study program regarding the online learning process for the English nursing course, along with the obstacles encountered and potential solutions to solve the obstacles. The questions of this study are; what are the perceptions of fourth-semester students in the nursing study program regarding the online learning process for the English nursing subject, what are the obstacles encountered in the online learning of the nursing English subject and what are the potential solutions to overcome these challenges? The research utilized a mixed-methods research method by administering questionnaires to all participants and interviewing 5 of them to collect data. The participants were selected by applying purposive sampling in choosing one out of two classes. There are 42 nursing students who actively participated in the English nursing course were chosen to become the participants of this study. The result shows that the students generally held positive perceptions of online learning in the Nursing English subject during the Covid-19 pandemic. They considered the utilization of online methods for teaching the subject to be acceptable and acknowledged the value of online learning as a viable alternative, particularly in the context of the pandemic. They also recognized that online learning had significant merits in the field of education, particularly when faced with obstacles such as the Covid-19 pandemic. Several obstacles were identified, including limitations in the interaction between teachers and students, inadequate network connectivity, the internet quota is limited due to financial aspects, substandard quality of mobile devices, minimal engagement during the lectures, causing adverse effects on students’ eye health, inadequate internal device memory, challenging in understanding the subject matter and limited monitoring of students. To address these, recommendations include: providing clear and structured materials, improving technical support, integrating interactive elements, balancing assignments with explanations, encouraging time management, creating engaging content, facilitating peer interactions, ensuring content accessibility, and establishing clear communication channels. These strategies mitigate challenges, ensuring a seamless learning experience that fosters holistic growth. In essence, this study underscores the significance of overcoming obstacles and implementing effective strategies to create a robust and supportive online learning environment for fourth-semester nursing students in the English nursing course.